Forming characteristics and precision control method of Ti60 titanium alloy ultra-thin hyperbolic shell in electro-assisted drawing - Renhai Yu; Shaofeng Liu; Pi Ling; Bosong Liu; Yingsheng Li; Lin Zhong; Kemin Xue (Journal of Materials Research and Technology)
The advancement of deep space exploration necessitates advanced upper stages with superior structural efficiency, flexibility, and reliability. However, the precise formation of titanium alloy ultra-thin hyperbolic shell remains a significant challenge in the aerospace sector. This study introduces a novel electro-assisted drawing forming technology, which enables rapid self-resistive heating and precise temperature-controlled drawing through the optimization of process parameters. The results demonstrate that the continuous application of pulse current for temperature compensation effectively maintains the deformation temperature of Ti60 alloy within the optimal range of 815–906 °C, reducing the temperature difference by 87.8 % compared to the no-current condition. Based on the material properties and deformation characteristics, the cause of springback is analyzed, and a springback prediction model is established. The model predicts that the difference in curvature radius is 1.7 mm and 1.1 mm under current densities of 11.5 and 12 A/mm2. Notably, the hyperbolic shell manufactured using the parameter combination of AE + XD mode, 12 A/mm2, and 0.833 mm/s, which not only achieves a dual-phase microstructure but also demonstrates a maximum thinning rate of 3.6 %, and a curvature radius difference of only 1.5 mm. This parameter combination is identified as the optimal choice for manufacturing Ti60 alloy ultra-thin hyperbolic shell.